Serum epidermal growth factor levels in epithelial ovarian tumours - Sadłecki, Paweł; Walentowicz-Sadłecka, Małgorzata; Grabiec, Marek (Menopause Review/Przegląd Menopauzalny, 2011)
Background: Epithelial ovarian cancer is the leading cause of cancer deaths resulting from gynaecological malignancies. Like most other epithelial tumours, epithelial ovarian cancer spreads initially by direct extension into adjacent organs. EGF expression has been demonstrated in many solid tumours, including ovarian cancer. EGF and its receptor are involved in the process of tumour genesis and progression. EGF also stimulates angiogenesis, which is considered essential for tumour growth and the development of metastases. Aim of the study: The aim of our study was to determine the levels of EGF in the sera of patients with benign and malignant epithelial ovarian tumours. Methods: EGF serum concentrations were measured by ELISA test (Quantikine R&D). Results: The median EGF concentrations were found to be significantly higher in the sera of ovarian cancers than in benign tumours. Conclusion : Pre treatment EGF serum levels might be regarded as an additional tool in the differentiation of ovarian tumours.